In the eyes of the beholder: Race, place and health - Velasquez, Alfredo J.; Douglas, Jason A.; Guo, Fangqi; Robinette, Jennifer W. (Frontiers in Public Health, 2022)
Racial and ethnic health disparities are fundamentally connected to neighborhood quality. For example, as a result of historical systemic inequities, racial and ethnic minorities are more likely to live in neighborhoods with signs of physical disorder (e.g., graffiti, vandalism), and physically disordered environments have been noted to associate with increased risk for chronic illness. Varying degrees of exposure to neighborhood disorder may differ through which people perceive their neighborhoods, however, with those most exposed (e.g., historically marginalized racial/ethnic groups) perhaps perceiving less threat from signs of neighborhood disorder. The purpose of the present study was to examine the complex interrelationships between people and place by investigating whether exposure to neighborhood physical disorder relates to residents’ (1) perceptions of neighborhood safety and (2) perceptions of their health, and (3) examining whether these links vary by race/ethnicity. Using 2016-2018 Health and Retirement Study (HRS) data, a representative sample of US adults aged 51 years and older (n= 9,080, mean age 68 years), we conducted a series of weighted linear regressions to examine the role of neighborhood disorder in relation to both perceived neighborhood safety and self-rated health. Results indicated that greater neighborhood physical disorder was statistically significantly related to feeling less safe among all racial/ethnic groups except non-Hispanic Blacks. Regarding self-rated health, neighborhood physical disorder was statistically significantly related to poorer health among all racial/ethnic groups. These findings suggest that, despite differential interpretation of neighborhood disorder as a threat to safety, this modifiable aspect of peoples’ environment is related to poor health regardless of one’s race/ethnicity.